Ablación endovenosa por radiofrecuencia en pacientes con insuficiencia venosa superficial del Hospital Isidro Ayora de Loja - Ortega Calderón, William Alexander (2019)
Superficial venous insufficiency is a chronic disease that causes disability and conventional surgical repair involves major complications. The purpose of this study is to know the clinical severity of superficial venous insufficiency according to the Clinical-Etiology-Anatomy-Pathophysiology classification (CEAP) and the insufficient venous system, also identify risk factors for superficial venous insufficiency, and establish the effectiveness and safety of intravenous radiofrequency ablation in patients treated in the outpatient vascular surgery service at Isidro Ayora Hospital of Loja during May - August 2019. It is a quantitative approach and cross-sectional study; developed in a population of 62 patients. Obtaining as results that the clinical degrees according to the CEAP classification, C3-edema (46.77%) and C2-trunk veins (24.19%), are the most frequent in the study population. The greater right (33.87%), bilateral (32.26%) and left (20.97%) saphenous veins constitute the most prevalent insufficient venous system. The most prevalent risk factors were female sex (74.19%), pregnancy history (72.58%), family history of superficial venous insufficiency (67.74%) and age between 35-64 years (66.12%). The effectiveness of radiofrequency ablation was absolute (100%), with high safety with a single case of deep venous thrombosis (1.61%), ecchymosis was present in all patients (100%) and with pain in low intensity (45.16%). We can conclude that superficial venous insufficiency is determined by female sex, history of pregnancy, advanced ages and that radiofrequency ablation is considered an effective and safe method of treatment. Keywords: Effectiveness, safety, major saphenous vein, deep venous thrombosis.